2018
DOI: 10.1007/s10900-018-0512-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Health Beliefs Among Hispanic Adults with Prediabetes

Abstract: Diabetes and prediabetes are increasing in prevalence, corresponding to epidemic rates of obesity. Hispanic adults with prediabetes are 1.7 times more likely than non-Hispanic whites to progress to diabetes. We set out to understand health beliefs of Hispanic adults and, with that knowledge, facilitate tailored messaging to promote patient activation and lifestyle change. Using the Risk Perception Survey for Developing Diabetes along with demographic and lifestyle intervention interest questions, a 34-question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…[ 7 17 ] Similarly, participants with higher educational attainment had higher baseline knowledge; previous studies have found high educational attainment to be associated with high health-related knowledge and health literacy. [ 26 ] It has to be noted that 43% of our sample reported having no or less than high school education, but there were statistically significant improvements in their knowledge levels after attending the health educational sessions. The significant change in knowledge levels has implications in the provisions of continuous health education in the community that lacks exposure to such activities otherwise.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…[ 7 17 ] Similarly, participants with higher educational attainment had higher baseline knowledge; previous studies have found high educational attainment to be associated with high health-related knowledge and health literacy. [ 26 ] It has to be noted that 43% of our sample reported having no or less than high school education, but there were statistically significant improvements in their knowledge levels after attending the health educational sessions. The significant change in knowledge levels has implications in the provisions of continuous health education in the community that lacks exposure to such activities otherwise.…”
Section: Discussionmentioning
confidence: 85%
“…Several studies looked at knowledge level among Latinos on gamut of health-related topics such as oral health, ocular health, diabetes risk, and cancer. [ 24 25 26 27 28 ] However, educational interventions to improve knowledge levels were limited and only included patients already seeking healthcare and lacked diversity in sample characteristics. [ 29 30 31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Most publications reviewed for risk perception of developing diabetes did not provide a formal definition for risk perception or reference any theories (Table 3). Studies providing meager definitions for perceived diabetes risk used terminology previously presented in other uses of risk perception but added descriptions of attitudes or beliefs towards diabetes, a “mental model,” 29 p. 1051 or self‐assessed diabetes risk 30‐37 . Only one study provided a robust definition of risk perception as “a complex term with multiple dimensions,” 5 p. 2543 including the vulnerability to (probability of) diabetes, severity of diabetes, level of personal control, comparative risk perceptions of other diseases and environmental factors.…”
Section: Resultsmentioning
confidence: 99%
“…There were 11 quantitative studies and one mixed-method study (Kullgren et al, 2016). There were three randomized control trial (RCTs; (Dorman et al, 2012; Voils et al, 2015; Wu et al, 2017), and eight cross-sectional descriptive studies (Fukuoka et al, 2015; Joiner, Sternberg, Kennedy, Chen, et al, 2016; Joiner, Sternberg, Kennedy, Fukuoka, et al, 2016; Piccinino et al, 2015; Seaborn et al, 2016; Shaak et al, 2018; Simonds et al, 2017; Yang et al, 2018).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Asian participants comprised approximately 5% of the sample of two studies (Wu et al, 2017; Yang et al, 2018) and more than 50% of another study (Fukuoka et al, 2015). Five studies did not specify the percentage of Asian participants (Dorman et al, 2012; Kullgren et al, 2016; Piccinino et al, 2015; Shaak et al, 2018; Voils et al, 2015). Four studies had samples of a single racial or ethnic background—none of which were Asian (Joiner, Sternberg, Kennedy, Chen, et al, 2016; Joiner, Sternberg, Kennedy, Fukuoka, et al, 2016; Seaborn et al, 2016; Simonds et al, 2017).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%